2009
DOI: 10.2754/avb200978020219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Selenium Source and Storage on Internal Quality of Eggs

Abstract: A 4-week experiment was carried out on 360 laying hens of the Hy Line Brown hybrid. Laying hens were divided into three groups (C, E 1 and E 2 ) with 120 hens in each group and kept in 24 cages. Hens were fed layer diets containing 18% of crude protein and 11.60 MJ ME. Hens in the control group C were fed diets that contained 0.2 mg/kg of inorganic selenium (sodium selenite). Experimental groups E 1 and E 2 were given diets with increased concentrations of selenium as follows: E 1 = 0.4 mg/kg of selenium (sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
2
11
0
1
Order By: Relevance
“…Albumen ( Results from this study partially agree with those reported by Skrivan et al (2006), Surai et al (2006) and Gajcevic et al (2009) and Kralik et al (2009); however, supplementation of diet with selenium was able to linearly increase (y = 3.09308 + 9.63459 x, r 2 = 0.52) the concentration of this mineral only in the albumen (Table 4). This fact can be explained by the selenomethionine role on protein synthesis and protein deposition in this portion of the egg.…”
Section: Factorsupporting
confidence: 91%
“…Albumen ( Results from this study partially agree with those reported by Skrivan et al (2006), Surai et al (2006) and Gajcevic et al (2009) and Kralik et al (2009); however, supplementation of diet with selenium was able to linearly increase (y = 3.09308 + 9.63459 x, r 2 = 0.52) the concentration of this mineral only in the albumen (Table 4). This fact can be explained by the selenomethionine role on protein synthesis and protein deposition in this portion of the egg.…”
Section: Factorsupporting
confidence: 91%
“…Some aspects of egg quality such as Haugh unit values are known to be adversely affected by the length of storage. However, the supplementation of diets for laying hens with organic Se source appears to be an effective tool positively influencing the indicators of egg freshness [28,32]. In such a way, the enrichment of eggs with Se can improve internal egg quality and decrease susceptibility of egg yolk to lipid peroxidation during storage [33].…”
Section: Discussionmentioning
confidence: 99%
“…Se concentration in diets affected significantly the content of Se in albumen and yolk (Kralik et al 2009). Eggs laid by hens contained 11-19 µg of Se, with more Se in the yolk.…”
Section: Selenium and Meat And Egg Qualitymentioning
confidence: 99%